EFFECT OF TRAINING, WORK DISCIPLINE AND WORK PLACEMENT ON EMPLOYEE PERFORMANCE - Yordan Aliran Dakhi; Fadilah Frimadani; Anugrah Indah Darmawan; Reymond Halomoan Silaen; Kristi Endah Ndilosa Ginting (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The direction of the research objective is to know simultaneously the effect of training, work discipline and work placement on employee performance at the University of Prima Indonesia.. Researchers use quantitative descriptive research using a questionnaire instrument aimed at the employees of the University of Prima Indonesia. Obtaining the multiple linear regression equation that is: Y = 2.292 + 0.531X1 + 0.234X2 + 0.123X3 +0. The tcount value of the Training variable is 6.707 and the ttable value is 1.992 (excel formula = TINV(0.05.75) then the tcount > ttable (6.707 > 1.992) and the sig value < 0.05. The t-count value of the Work Discipline variable is 2.892 and the ttable value is1,992 (Excel formula =TINV(0.05.75) then the value of tcount > ttable (2.892 > 1.992) and the value of sig < 0.05 and the t-count value of the Job Training variable is 2.069 and the t-table value is 1.992 (Excel formula =TINV(0.05.75) then the t-count value > t table (2,069 > 1,992) and the value of sig < 0.05 and the F value of the variable Training, Work Discipline and Job Training is 19,036and the value of Ftable is 2,493 (Excel formula = FINV(0.05,4,75) then the value of Fcount > Ftable (19,036 > 2,493) and sig value < 0,05. The value of RSquare is 0.825 or 82.50%, meaning that the research variable makes a major contribution or contribution in explaining the performance of the employees of Prima Indonesia University Medan by 82.50% while the remaining 17.50% is influenced by other factors. The conclusion of the study, Work Discipline Training, and Job Placement partially have a significant effect on Employee Performance at the Prima Indonesia University and simultaneously Training, Work Discipline and Work Placement have a significant effect on Employee Performance at Prima Indonesia University